2007
DOI: 10.1021/jp070397u
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the Ternary Phase Diagram for the Li−Cu−Sb System as the Anode Material for a Lithium Ion Battery

Abstract: Cu 2 Sb is known as a promising anode material for a lithium ion battery due to its good cycle performance and large volumetric capacity. In the present study we aimed to construct the ternary phase diagram for the Li-Cu-Sb system to elucidate the reaction mechanism upon charge-discharge reaction. In this procedure, a new intermediate phase of LiCuSb with a half-Heusler-type structure was found by combining experimental results with theoretical study. The obtained ternary phase diagram accounted for the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 20 publications
5
75
0
Order By: Relevance
“…As was recently shown [4,5] this problem can, however, be circumvented with materials composed of a mixture of Sb and Sb 2 O 3 nanoparticles obtained by electrodeposition from a solution containing antimony tartrate. As has been shown by several groups [27,[30][31][32][33][34], Cu 2 Sb can likewise be used as anode material in Li-ion batteries. According to Fransson et al.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…As was recently shown [4,5] this problem can, however, be circumvented with materials composed of a mixture of Sb and Sb 2 O 3 nanoparticles obtained by electrodeposition from a solution containing antimony tartrate. As has been shown by several groups [27,[30][31][32][33][34], Cu 2 Sb can likewise be used as anode material in Li-ion batteries. According to Fransson et al.…”
Section: Introductionmentioning
confidence: 82%
“…The Cu 2 Sb synthesized with the ceramic method which resulted in crystallite sizes larger than 200 nm did, on the other hand, not show corresponding structural reversibility. In addition, several reports have been published [30][31][32][33][34] in which Cu 2 Sb capacities significantly lower than the capacity reported by Fransson et al, have been found, most likely due to poor reversibility in reaction (1). The Cu 2 Sb lithiation and delithiation reaction mechanism has recently been discussed by several groups [30,32,35] and a three-step process has been proposed, in which the reaction (1) has been divided into two separate steps.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…First-principles computations were successfully applied to study the thermodynamics of alloys in early time, and by using Nernst equation, voltage profile can also be obtained [39]. Recently, the phase diagram for the Li-Cu-Sb ternary alloys has been constructed by combining XRD measurements and firstprinciples computations [40].…”
Section: Alloysmentioning
confidence: 99%
“…For Li-ion batteries, Cu 2 Sb was investigated as a source of Sb because its high capacity is comparable to that of graphite [5e7]. Cu 2 Sb undergoes a reversible Li-ion insertion/metal displacement reaction, ultimately leading to the formation of Li 3 Sb and Cu [5,6]. The reaction of a displacement electrode material is facilitated by using nanoparticles of an active material, which enhances the electronic and ionic pathways.…”
Section: Introductionmentioning
confidence: 99%